Pengaruh Massa Adsorben Batang Pisang Dan Waktu Kontak Adsorpsi Terhadap Efisiensi Penyisihan Fe Dan Kapasitas Adsorpsi Pada Pengolahan Air Gambut - Suziyana Suziyana; Syarfi Daud; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Air peat surface water that has a dark brown, is acid, levels of iron and manganese is high and has a high organic content. There are negative effects if used directly and continuously without treatment. The aim of this study is to calculate the removal efficiency of metal Fe on the peat water and calculate the adsorption capacity adsorbent of banana stems. Variables used in this study is a variation of the mass of adsorbent 1; 1,5; 2; 2,5 grams and a contact time of 15, 30, 60 and 90 minutes. The maximum removal for Fe metals occur in a mass of 2,5 grams and a contact time of 30 minutes with the adsorption efficiency of 80,31%. The adsorption capacity is 0,027 mg Fe / g on the mass of 1 gram with a contact time of 30 minutes. Type adsorbent banana stem adsorption Fe is Freundlich isotherm assumed coating formed multilayer by R2 of 0,989.Keywords: Adsorption, Peat water, Banana stems adsorbent, Adsorbent mass, Contact time